(When) should psychology be a science?. (21st July 2021) - Krpan, Dario
Abstract: Since its emergence in the 19 th century, academic psychology has striven to become accepted as a scientific discipline. This emphasis on "science" has led to many unprecedented advancements in the understanding of human behavior. However, the view that psychology must be approached as a science has become ingrained in the field over time, and critically discussing the implications of this notion has turned into a taboo. In this article, I examine the benefits and limitations of applying the scientific paradigm to psychology, and I propose when it is not optimal to approach psychology as a science if the field is to maximize its potential. Importantly, I do not imply that practicing psychology as a "non‐science" means practicing it as a pseudoscience. Quite to the contrary, I argue that not always enforcing the scientific viewpoint can prevent pseudoscientific practices and make the field more scientific in the long run.